CONTROLLING COLOR CONSISTENCY IN THE PRODUCTION PROCESS OF PACKAGING PRINT - Lala Hucadinota Ainul Amri; Untung Basuki; Galih Ruliftiawan (Kreator, 2022)
The printing industry is an industry that focuses on printing results. Controlling the consistency of print colors is a very important matter in order to be able to produce a package through printed packaging with good quality. Some aspects that affect color consistency are wetting water and engine maintenance, besides that there are still many aspects that have an effect. Good quality is seen from several factors and one of them is the color of the print. To produce good print quality, it is necessary to maintain color consistency during the printing process in order to minimize the possibility of printing out of color range. This study aims to find the factors that influence the consistency of the color of the packaging print. Descriptive method is used in this research, with the approach of field observations and in-depth interviews. Analysis of the results using the Fishbone diagram. The findings that have been recorded are several findings, both in print aspects, aspects that affect print color and problems controlling the consistency of print colors. Print aspects that need to be considered are colors, registers, and text. Aspects that affect the color of the print are wetting water, printing ink, machine, and ink roll. factors that must be considered in order to create a quality printed packaging that is consistent with color, including man, machine, material, method, measurement, and environment factors. The solution to this problem is to improve the quality of man, machine, material, method, measurement, and environment factors.Keywords— Control, Color Consistency, Print, Packaging